Vacuum-assisted breast biopsy of microcalcifications on the stereotactic prone table and comparison of the histopathologic diagnosis with mammographic features (Annals of Medical Research, 2021)
Aim: Breast cancer is one of the most important causes of mortality and morbidity in women. With the widespread use of screening mammography, the detection of non-palpable suspected cancerous lesions is increasing. Therefore, the use of vacuum-assisted breast biopsy in the management of breast lesions continues to increase. The aim of this study was to evaluate the histopathological results of suspicious microcalcifications which were diagnosed by vacuum-assisted needle biopsy on a stereotactic prone table and to compare the mammographic features of the microcalcifications with the histopathological results. Materials and Methods: The study included a total of 119 patients with a median age of 51 years (range, 33-77 years) who underwent stereotactic biopsy on a prone table because of suspicious microcalcifications between March 2010 and July 2014. Retrospective evaluation was made of the preoperative mammographic features, and the BI-RADS (Breast imaging-reporting and data system) scores of the microcalcifications and the vacuum biopsy and / or excisional histopathological results. Results: Stereotactic vacuum-assisted breast biopsy revealed that 52.1% of the lesions were benign and 47.9% were malignant. After vacuum-assisted stereotactic biopsy 61 patients underwent surgery. In 10 of these (16.3%) the final excisional histopathological diagnosis was benign, and in 51 (83.7%) malignancy was determined. Conclusion: Vacuum-assisted breast biopsy on a stereotactic prone table is a successful technique with a low failure rate for microcalcifications that are non-palpable and have no ultrasonographic findings.
Keywords: BI-RADS; mammography; microcalcifications; stereotactic vacuum biopsy